Effect of Citric Acid Application on Anatomical and Physiological Properties of the Vegetative Parts of a Species of Tamarindus Indica Cultivated in Iraq - Suha Dhia Twaij (Journal of Global Pharma Technology, 2019)
The present study included details of the anatomical properties of the vegetable parts of the stem, the cultured leaf in Iraq for some species of Tamarindus indica. The study examined the stomata index and the rate of both the length and width of the complex stomata and the thickness of the cuticle, the parenchymal and sclerenchymal tissue, phloem and xylem. It was taken the parts mentioned and measured after the treatment of the plant with citric acid and measured for the treated species with citric acid and untreated. The study showed that there is a clear variation in the properties above.